2017
DOI: 10.1017/s0033291717000071
|View full text |Cite
|
Sign up to set email alerts
|

Impaired awareness of motor intention in functional neurological disorder: implications for voluntary and functional movement

Abstract: BackgroundFunctional neurological disorders (FNDs), also known as conversion disorder, are unexplained neurological symptoms unrelated to a neurological cause. The disorder is common, yet poorly understood. The symptoms are experienced as involuntary but have similarities to voluntary processes. Here we studied intention awareness in FND.MethodA total of 26 FND patients and 25 healthy volunteers participated in this functional magnetic resonance study using Libet's clock.ResultsFND is characterized by delayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 54 publications
7
57
0
2
Order By: Relevance
“…28 29 Our functional propagation findings suggest that while the left anterior insula may be an important node in the pathophysiology of FND, a network perspective incorporating the impact of abnormal integration of information from the left anterior insula to the right anterior insula, TPJ and motor regions sheds additional light on brainsymptom severity relationships. In addition, tasked-based 6 55 and resting-state neuroimaging abnormalities [23][24][25] in the TPJ/inferior parietal lobule have been characterised in FND cohorts, and linked to impaired motor attention awareness and self-agency. Enhanced insular-TPJ link-step connectivity correlating with symptom severity in our study, and previously described taskbased 55 and functional connectivity alterations 25 across insular and TPJ areas, suggest that these epicentres both play important roles in promoting altered awareness in individuals with FND.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 29 Our functional propagation findings suggest that while the left anterior insula may be an important node in the pathophysiology of FND, a network perspective incorporating the impact of abnormal integration of information from the left anterior insula to the right anterior insula, TPJ and motor regions sheds additional light on brainsymptom severity relationships. In addition, tasked-based 6 55 and resting-state neuroimaging abnormalities [23][24][25] in the TPJ/inferior parietal lobule have been characterised in FND cohorts, and linked to impaired motor attention awareness and self-agency. Enhanced insular-TPJ link-step connectivity correlating with symptom severity in our study, and previously described taskbased 55 and functional connectivity alterations 25 across insular and TPJ areas, suggest that these epicentres both play important roles in promoting altered awareness in individuals with FND.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior portions of the multimodal integration network overlap with the salience network, while posterior areas of this network (eg, TPJ) are implicated in motor intention awareness and action authorship deficits in FND. [23][24][25] Notably, SFC has characterised mechanistic insights in neurologic 26 and neuropsychiatric populations. 27 In this resting-state neuroimaging study, we examined the functional propagation of primary motor (hand, foot, tongue) and amygdalar (laterobasal, centromedial nuclei) regions in 30 patients with motor FND compared with 30 healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing patients when they had their involuntary functional tics to a period where they had a voluntary tremor (order to reproduce their tremor intentionally), fMRI demonstrated a reduced brain activity in the right temporo-parietal junction (TPJ), a key area involved in integrating complex sensory signals [78,79]. The right TPJ plays an important role in the sense of agency, which is the sense that we are the actors of our own actions.…”
Section: Physiopathologymentioning
confidence: 99%
“…Studies using several experimental modalities have suggested an impairment in the sense of agency (SA) in patients with FMDs. Functional magnetic resonance imaging (fMRI) studies have shown decreased functional connectivity between the right temporoparietal junction (a critical region in the SA network) and sensorimotor regions in patients with FMDs compared to healthy controls . In another fMRI study in which a virtual reality paradigm was used to modulate SA for a motor control task in healthy control patients and those with FMD, the FMD group reported greater variability in their perceived level of control, associated with selective disruption of the SA network .…”
Section: Functional Movement Disordersmentioning
confidence: 99%